The Significance of Innovative Application of Foreign Pedagogic Methods - Gu, Peiyu (Science Insights Education Frontiers, 2024)
International educational conversations, an important component of cultural communication of humanity, play a significant role in advancing the education development of all countries and territories. Meanwhile, it is equally important to remember that all educational theories and practices derive from concrete contexts. The universalization of a well-acclaimed pedagogical method is not as easy as assumed (Yu & Li, 2010).